A method for laser cladding cobalt alloy coating on the inner wall of a pipeline with the assistance of a steady-state electromagnetic field

CN122979898APending Publication Date: 2026-10-27河南省锅炉压力容器检验技术科学研究院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611361765.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明的目的在于解决现有技术中激光熔覆钴合金涂层中晶粒和硬质相粗大导致强韧性不足的问题,提供一种稳态电磁场辅助激光熔覆管道内壁钴合金涂层的方法

Benefits of technology

本发明中稳态电磁场的恒定洛伦兹力促进熔液对流,增加硬质相与熔液的摩擦,降低其生长速率,克服了交变电磁场紊流状态导致分布不均和尺寸差异大的缺陷;CeO2变质剂增加非自发形核质点数量细化晶粒,WC颗粒形成硬质相。协同实现晶粒与硬质相的双重细化,使涂层综合性能显著提升,拉伸强度和冲击韧性提高30%以上,磨损率降低30%以上,有效延长了化工管道使用寿命,降低了设备维护和更换成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979898A_ABST
    Figure CN122979898A_ABST
Patent Text Reader

Abstract

The application discloses a kind of steady-state electromagnetic field auxiliary laser cladding pipeline inner wall cobalt alloy coating method, belong to metal surface engineering and laser additive manufacturing technical field.The method includes: the inner wall of heat-resistant steel pipeline is pretreated;CoCrMo alloy powder, WC powder and CeO2 Powder are mixed to prepare composite powder;Laser is used to carry out laser cladding treatment under the assistance of steady-state electromagnetic field, wherein the direction of steady-state magnetic field is perpendicular to laser scanning direction, the direction of steady-state electric field is parallel to laser scanning direction, and constant lorentz force is generated by the perpendicular to each other;After cladding, it is cooled with furnace.The constant lorentz force of steady-state electromagnetic field is used to promote melt convection, refine hard phase, cooperate CeO2 Grain refinement, WC forms hard phase, and realizes the dual refinement of grain and hard phase, so that the tensile strength and impact toughness of coating are improved by more than 30%, the wear rate is reduced by more than 30%, and it is suitable for surface strengthening and protection of the inner wall of chemical pipeline.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal surface engineering and laser additive manufacturing technology, and relates to a method for steady-state electromagnetic field-assisted laser cladding of cobalt alloy coating on the inner wall of a pipeline. Background Technology

[0002] Hard alloy coatings are an effective method to improve the surface properties of pipelines. Cobalt alloys, containing elements such as Cr, Ni, W, Mo, and Fe, possess excellent wear resistance, corrosion resistance, impact resistance, and high-temperature oxidation resistance, making them ideal materials for manufacturing wear- and corrosion-resistant pipeline coatings. However, traditional cladding techniques still face many problems: arc-welded coatings are prone to component segregation, resulting in insufficient wear resistance; thermally sprayed coatings have poor metallurgical bonding with the base alloy, making them prone to peeling off under significant impact.

[0003] Laser cladding, a novel surface modification technology, utilizes a high-energy laser beam to rapidly melt and cool alloy powder and the substrate surface layer, resulting in a dense, uniformly composed, and metallurgically bonded alloy coating. In recent years, laser cladding modification technology has been adopted for chemical pipelines, improving the wear and corrosion resistance of the pipeline inner wall to some extent. However, research shows that the grains and hard phases in laser-clad alloy coatings are coarse, leading to insufficient strength and toughness. Although adjusting laser process parameters and post-weld heat treatment can reduce the size of grains and hard phases, the grain refinement effect is limited, and the heat treatment process significantly increases production costs, hindering the widespread adoption of laser cladding technology in the chemical pipeline manufacturing field.

[0004] In existing technologies, progress has been made in the research of cobalt alloy coatings doped with WC powder. However, excessive WC particles can cause the cobalt alloy to become embrittled, and how to improve both the wear resistance and toughness of the cobalt alloy has become a research challenge. Rare earth element CeO2 can purify alloy impurities and refine grains, and has application value in the field of wear-resistant alloy surface modification. However, excessive CeO2 powder is prone to agglomeration and precipitation in the alloy coating. Electromagnetic field-assisted laser forming technology has been studied in refining the hard phase of alloy coatings, but problems exist such as uneven distribution of hard phase particles in the melt and large differences in particle size.

[0005] Therefore, developing a method that can simultaneously refine grains and hard phases and improve the strength, toughness and wear resistance of cobalt alloy coatings has important engineering application value for surface strengthening of the inner wall of chemical pipelines. Summary of the Invention

[0006] The purpose of this invention is to solve the problem of insufficient strength and toughness caused by coarse grains and hard phases in the existing laser cladding cobalt alloy coating, and to provide a method for laser cladding of cobalt alloy coating on the inner wall of a pipeline with steady-state electromagnetic field assistance.

[0007] To achieve the above objectives, the present invention employs the following technical solution: A method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe includes the following steps: S1, pre-treatment of the inner wall substrate material of heat-resistant steel pipe by grinding, cleaning and drying; S2, Prepare a composite powder by mixing CoCrMo alloy powder, WC powder, and CeO2 powder in a certain proportion; the WC powder has a particle size of 1.0-5.0 μm and is added at 10-40% of the total mass of the composite powder; the CeO2 powder has a particle size of 50-200 nm and is added at 1.0-3.0% of the total mass of the composite powder. S3 uses a laser as a heat source and a powder feeding device to transport the composite powder prepared in step two to the inner wall surface of the pipe. Laser cladding is then performed under the assistance of a steady-state electromagnetic field. The process parameters for laser cladding are: laser power 0.8-2.0KW, laser scanning rate 0.3-0.7m / min, powder feeding rate 4.0-12.0g / min, scanning spacing 0.8-1.6mm, overlap rate 30-50%, and preheating temperature 300-400℃. S4. During the laser cladding process, a steady-state electromagnetic field is applied through a steady-state electromagnetic field generator. The steady-state electromagnetic field includes a steady-state magnetic field and a steady-state electric field. The direction of the steady-state magnetic field is perpendicular to the laser scanning direction, and the direction of the steady-state electric field is parallel to the laser scanning direction. The magnetic field and electric field are perpendicular to each other, generating a constant Lorentz force that acts on the hard phase particles in the molten pool. The parameters of the steady-state electromagnetic field are: magnetic field strength 0.5-2.0T, DC current strength 0-200A, and electromagnetic field frequency 50-100Hz. S5. After laser cladding is completed, the pipeline is cooled to room temperature in a protective atmosphere to obtain a cobalt alloy coating on the inner wall of the pipeline.

[0008] The heat-resistant steel in S1 is 12Cr2Mo steel, and its chemical composition by mass percentage is: Cr 2.12%, Mo 0.32%, C 0.12%, Ni 0.4%, Fe (balance balance), Si 0.3%, Mn 0.84%, P 0.03%; the grinding is mechanical grinding until the surface roughness Ra ≤ 3.2μm; the cleaning is ultrasonic cleaning with acetone and anhydrous ethanol for 10-20 minutes each; and the drying temperature is 150-200℃.

[0009] The chemical composition of the CoCrMo alloy powder in S2, by mass percentage, is as follows: Co (balance balance), Cr 28.0%, Mo 6.2%, C 0.8%, Ni 0.5%, Fe 0.75%, W 0.2%, Si 1.2%, Mn 0.3%, P 0.03%, N 0.15%, with a particle size range of 45-150 μm. The mixing process involves placing the powder in a V-type powder mixer and mixing at a speed of 80-120 r / min for 4-6 hours, followed by drying in a vacuum drying oven at 80-100℃ for 2-4 hours.

[0010] The preferred particle size of the WC powder in S2 is 3.0 μm, and the amount added is 20% of the total mass of the composite powder; the preferred particle size of the CeO2 powder is 100 nm, and the amount added is 1.0% of the total mass of the composite powder.

[0011] The laser in S3 is a semiconductor laser with a wavelength of 1.07 μm and a laser spot diameter of 3-5 mm; the powder feeding device is a gas-carried powder feeder, and the powder feeding gas is argon; the protective atmosphere is argon, and the gas flow rate is 8-15 L / min.

[0012] In S3, the laser cladding adopts a multi-layer, multi-pass overlapping method, with a single layer cladding thickness of 0.8-1.5mm, a total number of cladding layers of 1-3 layers, a molten pool temperature controlled at 1200-1400℃, and a molten pool depth of 0.5-2.0mm.

[0013] The laser cladding process parameters are as follows: laser power 1.2KW, laser scanning rate 0.5m / min, powder feeding rate 4.0g / min, scanning interval 0.8mm, laser spot diameter 4mm, overlap rate 40%, preheating temperature 350℃, protective atmosphere is argon, and gas flow rate 12L / min.

[0014] The parameters of the steady-state electromagnetic field in S4 are: magnetic field strength 1.0T, DC current strength 100A, and electromagnetic field frequency 50Hz.

[0015] The protective atmosphere in S5 is argon, and the cooling method is furnace-in-flight cooling.

[0016] The cobalt alloy coating for the inner wall of the pipe prepared according to the aforementioned method is metallurgically bonded to the substrate. The coating has a grain size of 5-12 μm and a hard phase size of 2-6 μm, with the hard phase uniformly distributed throughout the coating. The cobalt alloy coating has a hardness of HV 0.5480-610, a tensile strength of 780-860 MPa, and an impact toughness of 45-52 J / cm². 2 The wear rate is 1.8-2.5×10⁻⁶. -6 mm 3 / (N·m).

[0017] Compared with the prior art, the present invention has the following beneficial effects: In this invention, the constant Lorentz force of the steady-state electromagnetic field promotes molten convection, increases friction between the hard phase and the molten metal, and reduces its growth rate, overcoming the defects of uneven distribution and large size differences caused by the turbulent state of the alternating electromagnetic field. The CeO2 modifier increases the number of non-spontaneous nucleation particles, refining the grains, while WC particles form the hard phase. This synergistic effect of grain and hard phase refinement significantly improves the overall performance of the coating, increasing tensile strength and impact toughness by more than 30%, reducing wear rate by more than 30%, effectively extending the service life of chemical pipelines, and reducing equipment maintenance and replacement costs.

[0018] This invention achieves high-performance coatings without subsequent heat treatment, avoiding the adverse effects of high-temperature heat treatment on the pipe substrate. It significantly shortens the production cycle, reduces energy consumption and manufacturing costs, and facilitates large-scale application. Furthermore, by adjusting steady-state electromagnetic field parameters and laser process parameters, along with flexible adjustments to the content of the composite modifier, the coating's microstructure can be precisely controlled, enabling on-demand adjustment of its toughness and wear resistance to meet the requirements of different operating conditions. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is a flowchart of the method for steady-state electromagnetic field-assisted laser cladding of cobalt alloy coating on the inner wall of a pipeline according to the present invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0022] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.

[0023] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.

[0024] The present invention will now be described in further detail with reference to the accompanying drawings: See Figure 1 The flowchart below shows the method for steady-state electromagnetic field-assisted laser cladding of cobalt alloy coating on the inner wall of a pipeline according to the present invention, which includes the following steps: S1 involves pre-treating the surface of the heat-resistant steel pipe's inner wall substrate material through grinding, cleaning, and drying. The heat-resistant steel in S1 is 12Cr2Mo steel, with the following chemical composition by mass percentage: Cr 2.12%, Mo 0.32%, C 0.12%, Ni 0.4%, Fe (balance balance), Si 0.3%, Mn 0.84%, and P 0.03%. Grinding is performed mechanically until the surface roughness Ra ≤ 3.2 μm. Cleaning involves sequential ultrasonic cleaning with acetone and anhydrous ethanol for 10-20 minutes each. The drying temperature is 150-200℃.

[0025] S2, a composite powder is prepared by mixing CoCrMo alloy powder, WC powder, and CeO2 powder in a certain proportion; the particle size of WC powder is 1.0-5.0 μm, and the addition amount is 10-40% of the total mass of the composite powder; the particle size of CeO2 powder is 50-200 nm, and the addition amount is 1.0-3.0% of the total mass of the composite powder; the chemical composition of the CoCrMo alloy powder in S2, by mass percentage, is: Co is the balance balance, Cr 28.0%, Mo 6.2%, C 0.8%, Ni 0.5%, Fe 0.75%, W 0.2%, Si 1.2%, Mn 0.3%, P 0.03%, N 0.15%, with a particle size range of 45-150 μm; the mixing is carried out by placing the powder in a V-type powder mixer and mixing at a speed of 80-120 r / min for 4-6 hours, and then drying in a vacuum drying oven at 80-100℃ for 2-4 hours.

[0026] The preferred particle size of the WC powder is 3.0 μm, and the addition amount is 20% of the total mass of the composite powder; the preferred particle size of the CeO2 powder is 100 nm, and the addition amount is 1.0% of the total mass of the composite powder.

[0027] In step S3, a laser is used as the heat source. The composite powder prepared in step two is transported to the inner wall surface of the pipe through a powder feeding device, and laser cladding is performed under the assistance of a steady-state electromagnetic field. The process parameters for laser cladding are: laser power 0.8-2.0KW, laser scanning rate 0.3-0.7m / min, powder feeding rate 4.0-12.0g / min, scanning interval 0.8-1.6mm, overlap rate 30-50%, and preheating temperature 300-400℃. The laser in step S3 is a semiconductor laser with a wavelength of 1.07μm and a laser spot diameter of 3-5mm. The powder feeding device is a gas-carrying powder feeder, and the powder feeding gas is argon. The protective atmosphere is argon with a gas flow rate of 8-15L / min.

[0028] Laser cladding adopts a multi-layer, multi-pass overlapping method. The thickness of a single cladding layer is 0.8-1.5mm, the total number of cladding layers is 1-3 layers, the molten pool temperature is controlled at 1200-1400℃, and the molten pool depth is 0.5-2.0mm.

[0029] The laser cladding process parameters are as follows: laser power 1.2KW, laser scanning rate 0.5m / min, powder feeding rate 4.0g / min, scanning interval 0.8mm, laser spot diameter 4mm, overlap rate 40%, preheating temperature 350℃, protective atmosphere is argon, and gas flow rate 12L / min.

[0030] S4. During the laser cladding process, a steady-state electromagnetic field is applied through a steady-state electromagnetic field generator. The steady-state electromagnetic field includes a steady-state magnetic field and a steady-state electric field. The direction of the steady-state magnetic field is perpendicular to the laser scanning direction, and the direction of the steady-state electric field is parallel to the laser scanning direction. The magnetic field and electric field are perpendicular to each other, generating a constant Lorentz force that acts on the hard phase particles in the molten pool. The parameters of the steady-state electromagnetic field are: magnetic field strength 0.5-2.0T, DC current strength 0-200A, electromagnetic field frequency 50-100Hz; the parameters of the steady-state electromagnetic field are: magnetic field strength 1.0T, DC current strength 100A, electromagnetic field frequency 50Hz.

[0031] S5. After laser cladding is completed, the pipeline is cooled to room temperature in a protective atmosphere to obtain a cobalt alloy coating on the inner wall of the pipeline. The protective atmosphere is argon, and the cooling method is furnace cooling.

[0032] The cobalt alloy coating for the inner wall of the pipe prepared according to the aforementioned method is metallurgically bonded to the substrate. The coating has a grain size of 5-12 μm and a hard phase size of 2-6 μm, with the hard phase uniformly distributed throughout the coating. The cobalt alloy coating has a hardness of HV 0.5480-610, a tensile strength of 780-860 MPa, and an impact toughness of 45-52 J / cm². 2 The wear rate is 1.8-2.5×10⁻⁶. -6 mm 3 / (N·m).

[0033] Example 1 This embodiment provides a method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipeline, including the following steps: (1) Pretreatment of matrix material: The inner wall of 12Cr2Mo steel pipe is used as the matrix material. Its chemical composition by mass percentage is: Cr 2.12%, Mo 0.32%, C 0.12%, Ni 0.4%, Fe as balance, Si 0.3%, Mn 0.84%, P 0.03%. The inner wall surface of the pipe is mechanically ground to a surface roughness Ra≤3.2μm, then ultrasonically cleaned with acetone for 15min, and then ultrasonically cleaned with anhydrous ethanol for 15min to remove surface oil and impurities. Finally, it is dried at 180℃ for later use.

[0034] (2) Preparation of composite powder, CoCrMo alloy powder was selected, and its chemical composition by mass percentage is as follows: Co is the balance balance, Cr 28.0%, Mo 6.2%, C 0.8%, Ni 0.5%, Fe 0.75%, W 0.2%, Si 1.2%, Mn 0.3%, P 0.03%, N 0.15%, with a particle size range of 45-150μm.

[0035] WC powder with a particle size of 3.0 μm was selected and added at 20% of the total mass of the composite powder. CeO2 powder with a particle size of 100 nm was selected and added at 1.0% of the total mass of the composite powder.

[0036] The above powder was placed in a V-type powder mixer and mixed at 100 r / min for 5 hours to obtain a uniformly mixed composite powder. The mixed composite powder was then dried in a vacuum drying oven at 90°C for 3 hours for later use.

[0037] (3) Laser cladding treatment: a semiconductor laser is used as the heat source with a laser wavelength of 1.07 μm. The composite powder is transported to the inner wall surface of the pipeline by a gas-carrying powder feeder. The powder feeding gas is argon. The pipeline is preheated to 350°C.

[0038] The laser cladding process parameters are as follows: laser power 1.2KW, laser scanning rate 0.5m / min, powder feeding rate 4.0g / min, scanning interval 0.8mm, laser spot diameter 4mm, overlap rate 40%, protective atmosphere is argon, gas flow rate 12L / min. A multi-layer, multi-pass overlap method is adopted, with a single layer cladding thickness of 1.0mm, two layers cladding, and the melt pool temperature controlled at 1200-1400℃.

[0039] (4) Steady-state electromagnetic field assistance: During the laser cladding process, a steady-state electromagnetic field is applied through a steady-state electromagnetic field generator. The direction of the steady-state magnetic field is perpendicular to the laser scanning direction, and the direction of the steady-state electric field is parallel to the laser scanning direction. The steady-state electromagnetic field parameters are: magnetic field strength 1.0T, DC current strength 100A, and electromagnetic field frequency 50Hz.

[0040] (5) Post-cladding treatment: After laser cladding is completed, the pipeline is cooled to room temperature in an argon protective atmosphere to obtain a cobalt alloy coating on the inner wall of the pipeline.

[0041] (6) Characterization of coating performance: The microstructure and performance of the cobalt alloy coating prepared in this embodiment were observed and tested. The results are as follows: The coating exhibits excellent metallurgical bonding with the substrate, with no cracks or porosity defects at the interface. The grain size in the coating is 5-8 μm, and the hard phase size is 2-4 μm. Compared to the control sample without an applied electromagnetic field and without added modifiers, the grain size is refined by approximately 55%, and the hard phase size by approximately 45%. The coating hardness is HV 0.5520-580, the tensile strength is 860 MPa, and the impact toughness is 52 J / cm². 2 The wear rate is 1.8 × 10⁻⁶. -6 mm 3 / (N·m). Compared with laser cladding cobalt alloy coatings without electromagnetic field application and without added modifier, the tensile strength is increased by 35%, the impact toughness is increased by 38%, and the wear rate is reduced by 36%.

[0042] Example 2 The difference between this embodiment and Embodiment 1 is that: the amount of WC powder added is 10% of the total mass of the composite powder, the amount of CeO2 powder added is 2.0% of the total mass of the composite powder, the particle size of WC powder is 1.0 μm, and the particle size of CeO2 powder is 50 nm. The laser power is 0.8 kW, the laser scanning rate is 0.3 m / min, the powder feeding rate is 8.0 g / min, and the scanning interval is 1.2 mm. The steady-state electromagnetic field parameters are: magnetic field strength 0.5 T, DC current strength 50 A, and electromagnetic field frequency 50 Hz.

[0043] The cobalt alloy coating prepared in this embodiment has a grain size of 8-12 μm, a hard phase size of 3-5 μm, a coating hardness of HV 0.5480-530, a tensile strength of 780 MPa, and an impact toughness of 45 J / cm. 2 The wear rate is 2.5 × 10⁻⁶. -6 mm 3 / (N·m).

[0044] Example 3 The difference between this embodiment and Embodiment 1 is that: the amount of WC powder added is 40% of the total mass of the composite powder, the amount of CeO2 powder added is 3.0% of the total mass of the composite powder, the particle size of WC powder is 5.0 μm, and the particle size of CeO2 powder is 200 nm. The laser power is 2.0 kW, the laser scanning rate is 0.7 m / min, the powder feeding rate is 12.0 g / min, and the scanning interval is 1.6 mm. The steady-state electromagnetic field parameters are: magnetic field strength 2.0 T, DC current strength 200 A, and electromagnetic field frequency 100 Hz.

[0045] The cobalt alloy coating prepared in this embodiment has a grain size of 6-10 μm, a hard phase size of 3-6 μm, a coating hardness of HV 0.5550-610, a tensile strength of 830 MPa, and an impact toughness of 48 J / cm. 2 The wear rate is 2.0 × 10⁻⁶. -6 mm 3 / (N·m).

[0046] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe, characterized in that, Includes the following steps: S1, pre-treatment of the inner wall substrate material of heat-resistant steel pipe by grinding, cleaning and drying; S2, Prepare a composite powder by mixing CoCrMo alloy powder, WC powder, and CeO2 powder in a certain proportion; the WC powder has a particle size of 1.0-5.0 μm and is added at 10-40% of the total mass of the composite powder; the CeO2 powder has a particle size of 50-200 nm and is added at 1.0-3.0% of the total mass of the composite powder. S3 uses a laser as a heat source and a powder feeding device to transport the composite powder prepared in step two to the inner wall surface of the pipe. Laser cladding is then performed under the assistance of a steady-state electromagnetic field. The process parameters for laser cladding are: laser power 0.8-2.0KW, laser scanning rate 0.3-0.7m / min, powder feeding rate 4.0-12.0g / min, scanning spacing 0.8-1.6mm, overlap rate 30-50%, and preheating temperature 300-400℃. S4. During the laser cladding process, a steady-state electromagnetic field is applied through a steady-state electromagnetic field generator. The steady-state electromagnetic field includes a steady-state magnetic field and a steady-state electric field. The direction of the steady-state magnetic field is perpendicular to the laser scanning direction, and the direction of the steady-state electric field is parallel to the laser scanning direction. The magnetic field and electric field are perpendicular to each other, generating a constant Lorentz force that acts on the hard phase particles in the molten pool. The parameters of the steady-state electromagnetic field are: magnetic field strength 0.5-2.0T, DC current strength 0-200A, and electromagnetic field frequency 50-100Hz. S5. After laser cladding is completed, the pipeline is cooled to room temperature in a protective atmosphere to obtain a cobalt alloy coating on the inner wall of the pipeline.

2. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, The heat-resistant steel in S1 is 12Cr2Mo steel, and its chemical composition by mass percentage is: Cr 2.12%, Mo 0.32%, C 0.12%, Ni 0.4%, Fe (balance balance), Si 0.3%, Mn 0.84%, P 0.03%; the grinding is mechanical grinding until the surface roughness Ra ≤ 3.2μm; the cleaning is ultrasonic cleaning with acetone and anhydrous ethanol for 10-20 minutes each; and the drying temperature is 150-200℃.

3. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, The chemical composition of the CoCrMo alloy powder in S2, by mass percentage, is as follows: Co is the balance, Cr 28.0%, Mo 6.2%, C 0.8%, Ni 0.5%, Fe 0.75%, W 0.2%, Si 1.2%, Mn 0.3%, P 0.03%, N 0.15%, with a particle size range of 45-150μm. The mixing process involves placing the powder in a V-type powder mixer and mixing at a speed of 80-120r / min for 4-6 hours, followed by drying in a vacuum drying oven at 80-100℃ for 2-4 hours.

4. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, The preferred particle size of the WC powder in S2 is 3.0 μm, and the amount added is 20% of the total mass of the composite powder; the preferred particle size of the CeO2 powder is 100 nm, and the amount added is 1.0% of the total mass of the composite powder.

5. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, The laser in S3 is a semiconductor laser with a wavelength of 1.07 μm and a laser spot diameter of 3-5 mm; the powder feeding device is a gas-carried powder feeder, and the powder feeding gas is argon; the protective atmosphere is argon, and the gas flow rate is 8-15 L / min.

6. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, In S3, the laser cladding adopts a multi-layer, multi-pass overlapping method, with a single layer cladding thickness of 0.8-1.5mm, a total number of cladding layers of 1-3 layers, a molten pool temperature controlled at 1200-1400℃, and a molten pool depth of 0.5-2.0mm.

7. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, The laser cladding process parameters are as follows: laser power 1.2KW, laser scanning rate 0.5m / min, powder feeding rate 4.0g / min, scanning interval 0.8mm, laser spot diameter 4mm, overlap rate 40%, preheating temperature 350℃, protective atmosphere is argon, and gas flow rate 12L / min.

8. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, The parameters of the steady-state electromagnetic field in S4 are: magnetic field strength 1.0T, DC current strength 100A, and electromagnetic field frequency 50Hz.

9. The method for steady-state electromagnetic field-assisted laser cladding of a cobalt alloy coating on the inner wall of a pipe as described in claim 1, characterized in that, The protective atmosphere in S5 is argon, and the cooling method is furnace-in-flight cooling.

10. The cobalt alloy coating on the inner wall of a pipe prepared by the method according to any one of claims 1-9, characterized in that: The cobalt alloy coating is metallurgically bonded to the substrate. The grain size in the coating is 5-12 μm, and the hard phase size is 2-6 μm, with the hard phase uniformly distributed throughout the coating. The cobalt alloy coating has a hardness of HV0.5 480-610, a tensile strength of 780-860 MPa, and an impact toughness of 45-52 J / cm². 2 The wear rate is 1.8-2.5×10⁻⁶. -6 mm 3 / (N·m).